Annual Research Review: What is resilience within the social ecology of human development?. (7th December 2012) - Ungar, Michael; Ghazinour, Mehdi; Richter, Jörg
<x xml:space="preserve">Abstract</x> Background: The development of Bronfenbrenner's bio‐social‐ecological systems model of human development parallels advances made to the theory of resilience that progressively moved from a more individual (micro) focus on traits to a multisystemic understanding of person–environment reciprocal processes. Methods: This review uses Bronfenbrenner's model and Ungar's social‐ecological interpretation of four decades of research on resilience to discuss the results of a purposeful selection of studies of resilience that have been done in different contexts and cultures. Results: An ecological model of resilience can, and indeed has been shown to help researchers of resilience to conceptualize the child's social and physical ecologies, from caregivers to neighbourhoods, that account for both proximal and distal factors that predict successful development under adversity. Three principles emerged from this review that inform a bio‐social‐ecological interpretation of resilience: equifinality (there are many proximal processes that can lead to many different, but equally viable, expressions of human development associated with well‐being); differential impact (the nature of the risks children face, their perceptions of the resources available to mitigate those risks and the quality of the resources that are accessible make proximal processes more or less influential to children's development); and contextual and cultural moderation (different contexts and cultures provide access to different processes associated with resilience as it is defined locally). Conclusion: As this review shows, using this multisystemic social‐ecological theory of resilience can inform a deeper understanding of the processes that contribute to positive development under stress. It can also offer practitioners and policy makers a broader perspective on principles for the design and implementation of effective interventions.